Latitudinal fluctuation in global concentration of CO2 and CH4 from shortwave infrared spectral observation by GOSAT during COVID-19 - Laxmi Kant Sharma; Rajani Kant Verma (International Journal of Digital Earth, 2021)
Various countries have rapidly implemented strict actions to slow the blowout of COVID-19. Many events were dis-regarded, and anthropogenic activities such as industrial and transport systems were at a stoppage. Many countries were on lockdown, including the largest emitters of carbon dioxide. Due to these lockdowns, anthropogenic activities have been reduced and reported that air quality improves at a regional scale in many countries, including India. Therefore, the current study using Greenhouse Gases Observing Satellite (GOSAT/IBUKI) datasets to monitor the fluctuation of the average global concentration of dry mole fractions of atmospheric Methane (CH4) and Carbon Dioxide (CO2) during these pandemic lockdowns from January to June 2020. Outputs emphasize no significant reduction in the average concentration of dry mole fractions of atmospheric CH4 over the globe, but a minor reduction was observed in global CO2 engagement. The average concentration of both gases compares at each ten-degree latitude. The study reveals that, against the regional breakdowns, these short time lockdowns are not enough to control the concentration of these greenhouse gases at a larger scale, such as 10˚ latitude and globally, except for a minor reduction in CO2 concentration.